Domestikasi Ikan Palapinang (Desmopuntius Pentazona) Pada Wadah Budidaya Terkontrol Dengan Pakan Buatan - Abisaputra Abisaputra; Faiz Fazaldi; Sutiatul Janah; Alexandria Christie Tampubolon; Ardiansyah Kurniawan (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This study aimed to evaluate the success of domestication of Palapinang fish (Desmopuntius pentazona) originating from wild populations through rearing in controlled containers. The observed parameters included adaptation to artificial feed, survival rate, growth performance, and water quality during the rearing period. Domestication is an important effort to reduce pressure on wild populations caused by intensive harvesting for the ornamental fish trade and habitat degradation due to post-tin mining activities on Bangka Island. A total of 30 fish with an average initial body weight of 0.85 g were reared for 30 days in a 30 L fiber tank containing 15 L of water sourced from their natural habitat. A descriptive method was applied, focusing on changes in feeding behavior and physiological adaptation during the domestication process. The results showed a survival rate of 60%, largely influenced by initial stress during transfer from the wild to the rearing system. The specific growth rate reached 2.68%/day with an absolute weight gain of 1.05 g, indicating effective utilization of artificial feed after the adaptation period. Adaptation to artificial feed occurred within 3–5 days, with feed consumption increasing steadily to more than 80% by the third week. Water quality remained within optimal ranges, with temperatures of 26–27°C, pH of 5–6, and dissolved oxygen of 8.0 mg/L, supporting physiological stability during the rearing period. Overall, the results indicate that Palapinang fish have strong potential for domestication and development in aquaculture systems as a sustainable conservation strategy.